Applied GIS. - Peterson, Jim; Wyatt, Ray (Monash University ePress, 2005)
An online peer-reviewed ejournal that publishes articles covering specific applications of GIS, demonstrating the deployment of spatial sciences in a wide range of environmental and social science contexts.